Komunikasi Pemasaran Hutan Bambu Sebagai Destinasi Wisata Kota Bekasi - Sukoco, Iwan; Prihadini, Diana; Suryani, Octavia (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
A tourist destination is a certain geographical area or area within one or more administrative areas that is distinct and has an element of tourist attraction. At this time many tourist spots do promotions with marketing communications. Marketing communication is a means used by companies in an effort to inform, persuade, and remind consumers both directly and indirectly about the products and brands they sell. The purpose of this study was to analyze the marketing communication strategies, marketing communication constraints, and marketing communication solutions that occur at Hutan Bambu Tourism Sites. This study used a qualitative approach with a descriptive method. The data were collected by interview, observation, and documentation. The results of this study indicated that the marketing promotion activities carried out by the Hutan Bambu Manager have not gone well, the indicator is because of the limited budget they have so Marketing Promotion activities cannot be carried out optimally.